Late Paleocene - early Eocene calcareous nannofossil relative abundance count data from IODP Site 378-U1553D (Campbell Plateau, SW Pacific Ocean) - Heather Jones; Bryan Niederbockstruck; Thomas Westerhold; Ursula Röhl (PANGAEA, 2025)
In this dataset, we show the raw relative abundance count data for calcareous nannofossils observed in sediment samples from International Ocean Discovery Program (IODP) Expedition 378, Site U1553, Hole D, located on the Campbell Plateau in the high paleolatitude SW Pacific Ocean. 66 smear slides spanning the late Paleocene - early Eocene (ca. 55.7 to 56.5 Ma) - including the Paleocene-Eocene Thermal Maximum (PETM) and an apparent pre-cursor event - were examined under a polarising light microscope at 1000 to 1600x magnification. At least 300 nannofossil specimens were counted in each sample and identified to species-level whenever possible (genus-level when not), predominantly using the taxonomic concepts collated in the online database Nannotax. Due to the presence of non-classic forms and intermediate morphotypes of species belonging to the Toweius/Prinsius evolutionary lineage, our taxonomic concepts for these taxa differed slightly from those presented on Nannotax and are therefore detailed further in the extquotesingleMethods extquotesingle section of the source text (Jones et al. 2025). Our genus-level relative abundance data were then used to document nannofossil assemblage change during the PETM and pre-cursor event using the previously-published age model and bulk sediment carbon isotope data in Niederbockstruck et al. (2024). After Hellinger data standardisation, the genus-level raw data were also used in a two-way cluster analysis and multiple Principal Components Analyses (PCA) extquotesingles to better visualise distinct paleoecological groups as Site U1553 and to compare our data to nannofossil assemblage data from other sites.